2022
DOI: 10.1002/anie.202202674
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Trisubstituted Alkenes by Nickel‐Catalyzed Benzylation and Alkene Isomerization

Abstract: Catalytic strategies that provide stereoselective access to highly substituted alkenes from abundant monosubstituted substrates are exceedingly sought-after but rare. Here, we show that a N-heterocyclic carbene-Ni I catalytic species mediates efficient union of electronically polarized terminal olefins with benzyl chlorides, in the presence of trimethylsilyl triflate and trimethylamine additives, to generate trisubstituted boron-and arene-containing trans alkenes in excellent regio-and stereoselectivities. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…An initial insertion of the alkene into the Ni-H bond generates an alkyl-Ni intermediate, which can react with the Scheme 8 Ni(I)/IPr-catalysed Heck-type benzylation/isomerisation for stereoselective synthesis of tri-substituted alkenes. 48 desired electrophile (via insertion or oxidative addition). Subsequent b-hydride elimination or reductive elimination affords the final product (Scheme 9b).…”
Section: Hydrofunctionalisation Of Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial insertion of the alkene into the Ni-H bond generates an alkyl-Ni intermediate, which can react with the Scheme 8 Ni(I)/IPr-catalysed Heck-type benzylation/isomerisation for stereoselective synthesis of tri-substituted alkenes. 48 desired electrophile (via insertion or oxidative addition). Subsequent b-hydride elimination or reductive elimination affords the final product (Scheme 9b).…”
Section: Hydrofunctionalisation Of Alkenesmentioning
confidence: 99%
“…An extension to their previous work (Scheme 7), Koh and co-workers reported a Ni(I)/IPr catalysed branched-selective Heck-type benzylation-stereoselective olefin isomerisation methodology to access tri-substituted alkenes. 48 The same dinuclear IPr-derived Ni(I) dimeric complex (25) was used as the precatalyst, which efficiently enabled the reaction of styrenes/vinylboronates with various functionalised benzyl chlorides under basic conditions, to afford trisubstituted alkenes with high trans-selectivity. The excellent branched selectivity (where the benzyl group is attached to the more substituted olefinic carbon) of the initial Heck-type benzylation is attributed to the steric control provided by the bulky NHC ligand, which effectively overrides the olefin's strong electronic bias for linear selectivity.…”
Section: Heck-type Reactionmentioning
confidence: 99%
“…[85,86,88,92] Some elegants Ni-catalyzed tandem processes incorporating a key isomerization step have also been described as a synthetically useful route towards this family of building blocks. [94,97] Never-theless, less attention has been given to this strategy using iron-based catalysts. In 2021, it was reported that structurally-defined iron(II) dichloride complexes 4-FeCl 2 and 5-FeCl 2 bearing a pincer phosphinepyridine-oxazoline or -imidazole framework were competent catalysts for the regio-and stereoselective monoisomerization of α-alkyl styrenes [144] (Scheme 10) and 1,1-disubstituted alkenyl boronates [145] (Scheme 11) respectively upon activation with NaH-BEt 3 .…”
Section: Iron Non-carbonyl Complexesmentioning
confidence: 99%
“…Such a technically simple and energy-efficient protocol opens a new avenue for a greener synthesis of higher substituted olefins from simple abundant terminal olefins. It saved the cost and availability problems of the alkenyl reagents in the Heck reaction and related variations (strictly speaking, that is a mechanistically different HA product synthesis method, not a standard HA). , This is essential in larger-scale synthesis and functionalized poly­(isobutylene) development.…”
Section: Catalyst Development and The First T-t Cross-ha Of Styrenes ...mentioning
confidence: 99%